PERTANGGUNGJAWABAN PIDANA PELAKU KLEPTOMANIA: KAJIAN KUHP DAN UNDANG-UNDANG KESEHATAN DALAM KASUS PILOT WINGS AIR - Surya Kurnia Kale Mira; Rudepel Petrus Leo; Bhisa Vitus Wilhelmus (Petitum Law Journal, 2026)
This study found that although the Indonesian Penal Code, particularly Article 44, allows for the exclusion of criminal liability for individuals with mental disorders, its practical application by the courts remains inconsistent. In the case involving a Wings Air pilot diagnosed with kleptomania—a psychiatric condition marked by an uncontrollable urge to steal—the court still imposed a criminal sentence. This was despite medical assessments indicating that the disorder could impair the individual’s mental capacity to form criminal intent (mens rea). Such a judicial outcome reveals a gap between the legal framework and its enforcement, where medical evaluations are not fully integrated into legal reasoning. The Health Law, which outlines more precise criteria for assessing mental health conditions, is not yet optimally utilized in legal proceedings. Therefore, the case underscores the need for a more cohesive interplay between legal principles and medical insight to ensure a fair and substantively just legal process for offenders with psychiatric conditions.